Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
File size: 15,278 Bytes
4365a98 |
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342 343 344 345 346 347 348 349 350 351 352 353 354 355 356 357 358 359 360 361 362 363 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 382 383 384 385 386 |
/-
Copyright (c) 2018 Kenny Lau. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Kenny Lau
-/
import data.fin.vec_notation
import logic.equiv.basic
/-!
# Equivalences for `fin n`
-/
universes u
variables {m n : ℕ}
/-- Equivalence between `fin 0` and `empty`. -/
def fin_zero_equiv : fin 0 ≃ empty :=
equiv.equiv_empty _
/-- Equivalence between `fin 0` and `pempty`. -/
def fin_zero_equiv' : fin 0 ≃ pempty.{u} :=
equiv.equiv_pempty _
/-- Equivalence between `fin 1` and `unit`. -/
def fin_one_equiv : fin 1 ≃ unit :=
equiv.equiv_punit _
/-- Equivalence between `fin 2` and `bool`. -/
def fin_two_equiv : fin 2 ≃ bool :=
{ to_fun := ![ff, tt],
inv_fun := λ b, cond b 1 0,
left_inv := fin.forall_fin_two.2 $ by simp,
right_inv := bool.forall_bool.2 $ by simp }
/-- `Π i : fin 2, α i` is equivalent to `α 0 × α 1`. See also `fin_two_arrow_equiv` for a
non-dependent version and `prod_equiv_pi_fin_two` for a version with inputs `α β : Type u`. -/
@[simps {fully_applied := ff}] def pi_fin_two_equiv (α : fin 2 → Type u) : (Π i, α i) ≃ α 0 × α 1 :=
{ to_fun := λ f, (f 0, f 1),
inv_fun := λ p, fin.cons p.1 $ fin.cons p.2 fin_zero_elim,
left_inv := λ f, funext $ fin.forall_fin_two.2 ⟨rfl, rfl⟩,
right_inv := λ ⟨x, y⟩, rfl }
lemma fin.preimage_apply_01_prod {α : fin 2 → Type u} (s : set (α 0)) (t : set (α 1)) :
(λ f : Π i, α i, (f 0, f 1)) ⁻¹' s ×ˢ t =
set.pi set.univ (fin.cons s $ fin.cons t fin.elim0) :=
begin
ext f,
have : (fin.cons s (fin.cons t fin.elim0) : Π i, set (α i)) 1 = t := rfl,
simp [fin.forall_fin_two, this]
end
lemma fin.preimage_apply_01_prod' {α : Type u} (s t : set α) :
(λ f : fin 2 → α, (f 0, f 1)) ⁻¹' s ×ˢ t = set.pi set.univ ![s, t] :=
fin.preimage_apply_01_prod s t
/-- A product space `α × β` is equivalent to the space `Π i : fin 2, γ i`, where
`γ = fin.cons α (fin.cons β fin_zero_elim)`. See also `pi_fin_two_equiv` and
`fin_two_arrow_equiv`. -/
@[simps {fully_applied := ff }] def prod_equiv_pi_fin_two (α β : Type u) :
α × β ≃ Π i : fin 2, ![α, β] i :=
(pi_fin_two_equiv (fin.cons α (fin.cons β fin_zero_elim))).symm
/-- The space of functions `fin 2 → α` is equivalent to `α × α`. See also `pi_fin_two_equiv` and
`prod_equiv_pi_fin_two`. -/
@[simps { fully_applied := ff }] def fin_two_arrow_equiv (α : Type*) : (fin 2 → α) ≃ α × α :=
{ inv_fun := λ x, ![x.1, x.2],
.. pi_fin_two_equiv (λ _, α) }
/-- `Π i : fin 2, α i` is order equivalent to `α 0 × α 1`. See also `order_iso.fin_two_arrow_equiv`
for a non-dependent version. -/
def order_iso.pi_fin_two_iso (α : fin 2 → Type u) [Π i, preorder (α i)] :
(Π i, α i) ≃o α 0 × α 1 :=
{ to_equiv := pi_fin_two_equiv α,
map_rel_iff' := λ f g, iff.symm fin.forall_fin_two }
/-- The space of functions `fin 2 → α` is order equivalent to `α × α`. See also
`order_iso.pi_fin_two_iso`. -/
def order_iso.fin_two_arrow_iso (α : Type*) [preorder α] : (fin 2 → α) ≃o α × α :=
{ to_equiv := fin_two_arrow_equiv α, .. order_iso.pi_fin_two_iso (λ _, α) }
/-- The 'identity' equivalence between `fin n` and `fin m` when `n = m`. -/
def fin_congr {n m : ℕ} (h : n = m) : fin n ≃ fin m :=
(fin.cast h).to_equiv
@[simp] lemma fin_congr_apply_mk {n m : ℕ} (h : n = m) (k : ℕ) (w : k < n) :
fin_congr h ⟨k, w⟩ = ⟨k, by { subst h, exact w }⟩ :=
rfl
@[simp] lemma fin_congr_symm {n m : ℕ} (h : n = m) :
(fin_congr h).symm = fin_congr h.symm := rfl
@[simp] lemma fin_congr_apply_coe {n m : ℕ} (h : n = m) (k : fin n) :
(fin_congr h k : ℕ) = k :=
by { cases k, refl, }
lemma fin_congr_symm_apply_coe {n m : ℕ} (h : n = m) (k : fin m) :
((fin_congr h).symm k : ℕ) = k :=
by { cases k, refl, }
/-- An equivalence that removes `i` and maps it to `none`.
This is a version of `fin.pred_above` that produces `option (fin n)` instead of
mapping both `i.cast_succ` and `i.succ` to `i`. -/
def fin_succ_equiv' {n : ℕ} (i : fin (n + 1)) :
fin (n + 1) ≃ option (fin n) :=
{ to_fun := i.insert_nth none some,
inv_fun := λ x, x.cases_on' i (fin.succ_above i),
left_inv := λ x, fin.succ_above_cases i (by simp) (λ j, by simp) x,
right_inv := λ x, by cases x; dsimp; simp }
@[simp] lemma fin_succ_equiv'_at {n : ℕ} (i : fin (n + 1)) :
(fin_succ_equiv' i) i = none := by simp [fin_succ_equiv']
@[simp] lemma fin_succ_equiv'_succ_above {n : ℕ} (i : fin (n + 1)) (j : fin n) :
fin_succ_equiv' i (i.succ_above j) = some j :=
@fin.insert_nth_apply_succ_above n (λ _, option (fin n)) i _ _ _
lemma fin_succ_equiv'_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) :
(fin_succ_equiv' i) m.cast_succ = some m :=
by rw [← fin.succ_above_below _ _ h, fin_succ_equiv'_succ_above]
lemma fin_succ_equiv'_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) :
(fin_succ_equiv' i) m.succ = some m :=
by rw [← fin.succ_above_above _ _ h, fin_succ_equiv'_succ_above]
@[simp] lemma fin_succ_equiv'_symm_none {n : ℕ} (i : fin (n + 1)) :
(fin_succ_equiv' i).symm none = i := rfl
@[simp] lemma fin_succ_equiv'_symm_some {n : ℕ} (i : fin (n + 1)) (j : fin n) :
(fin_succ_equiv' i).symm (some j) = i.succ_above j :=
rfl
lemma fin_succ_equiv'_symm_some_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) :
(fin_succ_equiv' i).symm (some m) = m.cast_succ :=
fin.succ_above_below i m h
lemma fin_succ_equiv'_symm_some_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) :
(fin_succ_equiv' i).symm (some m) = m.succ :=
fin.succ_above_above i m h
lemma fin_succ_equiv'_symm_coe_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) :
(fin_succ_equiv' i).symm m = m.cast_succ :=
fin_succ_equiv'_symm_some_below h
lemma fin_succ_equiv'_symm_coe_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) :
(fin_succ_equiv' i).symm m = m.succ :=
fin_succ_equiv'_symm_some_above h
/-- Equivalence between `fin (n + 1)` and `option (fin n)`.
This is a version of `fin.pred` that produces `option (fin n)` instead of
requiring a proof that the input is not `0`. -/
def fin_succ_equiv (n : ℕ) : fin (n + 1) ≃ option (fin n) :=
fin_succ_equiv' 0
@[simp] lemma fin_succ_equiv_zero {n : ℕ} :
(fin_succ_equiv n) 0 = none :=
rfl
@[simp] lemma fin_succ_equiv_succ {n : ℕ} (m : fin n):
(fin_succ_equiv n) m.succ = some m :=
fin_succ_equiv'_above (fin.zero_le _)
@[simp] lemma fin_succ_equiv_symm_none {n : ℕ} :
(fin_succ_equiv n).symm none = 0 :=
fin_succ_equiv'_symm_none _
@[simp] lemma fin_succ_equiv_symm_some {n : ℕ} (m : fin n) :
(fin_succ_equiv n).symm (some m) = m.succ :=
congr_fun fin.succ_above_zero m
@[simp] lemma fin_succ_equiv_symm_coe {n : ℕ} (m : fin n) :
(fin_succ_equiv n).symm m = m.succ :=
fin_succ_equiv_symm_some m
/-- The equiv version of `fin.pred_above_zero`. -/
lemma fin_succ_equiv'_zero {n : ℕ} :
fin_succ_equiv' (0 : fin (n + 1)) = fin_succ_equiv n := rfl
/-- `equiv` between `fin (n + 1)` and `option (fin n)` sending `fin.last n` to `none` -/
def fin_succ_equiv_last {n : ℕ} : fin (n + 1) ≃ option (fin n) :=
fin_succ_equiv' (fin.last n)
@[simp] lemma fin_succ_equiv_last_cast_succ {n : ℕ} (i : fin n) :
fin_succ_equiv_last i.cast_succ = some i :=
fin_succ_equiv'_below i.2
@[simp] lemma fin_succ_equiv_last_last {n : ℕ} :
fin_succ_equiv_last (fin.last n) = none :=
by simp [fin_succ_equiv_last]
@[simp] lemma fin_succ_equiv_last_symm_some {n : ℕ} (i : fin n) :
fin_succ_equiv_last.symm (some i) = i.cast_succ :=
fin_succ_equiv'_symm_some_below i.2
@[simp] lemma fin_succ_equiv_last_symm_coe {n : ℕ} (i : fin n) :
fin_succ_equiv_last.symm ↑i = i.cast_succ :=
fin_succ_equiv'_symm_some_below i.2
@[simp] lemma fin_succ_equiv_last_symm_none {n : ℕ} :
fin_succ_equiv_last.symm none = fin.last n :=
fin_succ_equiv'_symm_none _
/-- Equivalence between `Π j : fin (n + 1), α j` and `α i × Π j : fin n, α (fin.succ_above i j)`. -/
@[simps { fully_applied := ff}]
def equiv.pi_fin_succ_above_equiv {n : ℕ} (α : fin (n + 1) → Type u) (i : fin (n + 1)) :
(Π j, α j) ≃ α i × (Π j, α (i.succ_above j)) :=
{ to_fun := λ f, (f i, λ j, f (i.succ_above j)),
inv_fun := λ f, i.insert_nth f.1 f.2,
left_inv := λ f, by simp [fin.insert_nth_eq_iff],
right_inv := λ f, by simp }
/-- Order isomorphism between `Π j : fin (n + 1), α j` and
`α i × Π j : fin n, α (fin.succ_above i j)`. -/
def order_iso.pi_fin_succ_above_iso {n : ℕ} (α : fin (n + 1) → Type u) [Π i, has_le (α i)]
(i : fin (n + 1)) :
(Π j, α j) ≃o α i × (Π j, α (i.succ_above j)) :=
{ to_equiv := equiv.pi_fin_succ_above_equiv α i,
map_rel_iff' := λ f g, i.forall_iff_succ_above.symm }
/-- Equivalence between `fin (n + 1) → β` and `β × (fin n → β)`. -/
@[simps { fully_applied := ff}]
def equiv.pi_fin_succ (n : ℕ) (β : Type u) :
(fin (n+1) → β) ≃ β × (fin n → β) :=
equiv.pi_fin_succ_above_equiv (λ _, β) 0
/-- Equivalence between `fin m ⊕ fin n` and `fin (m + n)` -/
def fin_sum_fin_equiv : fin m ⊕ fin n ≃ fin (m + n) :=
{ to_fun := sum.elim (fin.cast_add n) (fin.nat_add m),
inv_fun := λ i, @fin.add_cases m n (λ _, fin m ⊕ fin n) sum.inl sum.inr i,
left_inv := λ x, by { cases x with y y; dsimp; simp },
right_inv := λ x, by refine fin.add_cases (λ i, _) (λ i, _) x; simp }
@[simp] lemma fin_sum_fin_equiv_apply_left (i : fin m) :
(fin_sum_fin_equiv (sum.inl i) : fin (m + n)) = fin.cast_add n i := rfl
@[simp] lemma fin_sum_fin_equiv_apply_right (i : fin n) :
(fin_sum_fin_equiv (sum.inr i) : fin (m + n)) = fin.nat_add m i := rfl
@[simp] lemma fin_sum_fin_equiv_symm_apply_cast_add (x : fin m) :
fin_sum_fin_equiv.symm (fin.cast_add n x) = sum.inl x :=
fin_sum_fin_equiv.symm_apply_apply (sum.inl x)
@[simp] lemma fin_sum_fin_equiv_symm_apply_nat_add (x : fin n) :
fin_sum_fin_equiv.symm (fin.nat_add m x) = sum.inr x :=
fin_sum_fin_equiv.symm_apply_apply (sum.inr x)
@[simp] lemma fin_sum_fin_equiv_symm_last :
fin_sum_fin_equiv.symm (fin.last n) = sum.inr 0 :=
fin_sum_fin_equiv_symm_apply_nat_add 0
/-- The equivalence between `fin (m + n)` and `fin (n + m)` which rotates by `n`. -/
def fin_add_flip : fin (m + n) ≃ fin (n + m) :=
(fin_sum_fin_equiv.symm.trans (equiv.sum_comm _ _)).trans fin_sum_fin_equiv
@[simp] lemma fin_add_flip_apply_cast_add (k : fin m) (n : ℕ) :
fin_add_flip (fin.cast_add n k) = fin.nat_add n k :=
by simp [fin_add_flip]
@[simp] lemma fin_add_flip_apply_nat_add (k : fin n) (m : ℕ) :
fin_add_flip (fin.nat_add m k) = fin.cast_add m k :=
by simp [fin_add_flip]
@[simp] lemma fin_add_flip_apply_mk_left {k : ℕ} (h : k < m)
(hk : k < m + n := nat.lt_add_right k m n h)
(hnk : n + k < n + m := add_lt_add_left h n) :
fin_add_flip (⟨k, hk⟩ : fin (m + n)) = ⟨n + k, hnk⟩ :=
by convert fin_add_flip_apply_cast_add ⟨k, h⟩ n
@[simp] lemma fin_add_flip_apply_mk_right {k : ℕ} (h₁ : m ≤ k) (h₂ : k < m + n) :
fin_add_flip (⟨k, h₂⟩ : fin (m + n)) = ⟨k - m, tsub_le_self.trans_lt $ add_comm m n ▸ h₂⟩ :=
begin
convert fin_add_flip_apply_nat_add ⟨k - m, (tsub_lt_iff_right h₁).2 _⟩ m,
{ simp [add_tsub_cancel_of_le h₁] },
{ rwa add_comm }
end
/-- Rotate `fin n` one step to the right. -/
def fin_rotate : Π n, equiv.perm (fin n)
| 0 := equiv.refl _
| (n+1) := fin_add_flip.trans (fin_congr (add_comm _ _))
lemma fin_rotate_of_lt {k : ℕ} (h : k < n) :
fin_rotate (n+1) ⟨k, lt_of_lt_of_le h (nat.le_succ _)⟩ = ⟨k + 1, nat.succ_lt_succ h⟩ :=
begin
dsimp [fin_rotate],
simp [h, add_comm],
end
lemma fin_rotate_last' : fin_rotate (n+1) ⟨n, lt_add_one _⟩ = ⟨0, nat.zero_lt_succ _⟩ :=
begin
dsimp [fin_rotate],
rw fin_add_flip_apply_mk_right,
simp,
end
lemma fin_rotate_last : fin_rotate (n+1) (fin.last _) = 0 :=
fin_rotate_last'
lemma fin.snoc_eq_cons_rotate {α : Type*} (v : fin n → α) (a : α) :
@fin.snoc _ (λ _, α) v a = (λ i, @fin.cons _ (λ _, α) a v (fin_rotate _ i)) :=
begin
ext ⟨i, h⟩,
by_cases h' : i < n,
{ rw [fin_rotate_of_lt h', fin.snoc, fin.cons, dif_pos h'],
refl, },
{ have h'' : n = i,
{ simp only [not_lt] at h', exact (nat.eq_of_le_of_lt_succ h' h).symm, },
subst h'',
rw [fin_rotate_last', fin.snoc, fin.cons, dif_neg (lt_irrefl _)],
refl, }
end
@[simp] lemma fin_rotate_zero : fin_rotate 0 = equiv.refl _ := rfl
@[simp] lemma fin_rotate_one : fin_rotate 1 = equiv.refl _ :=
subsingleton.elim _ _
@[simp] lemma fin_rotate_succ_apply {n : ℕ} (i : fin n.succ) :
fin_rotate n.succ i = i + 1 :=
begin
cases n,
{ simp },
rcases i.le_last.eq_or_lt with rfl|h,
{ simp [fin_rotate_last] },
{ cases i,
simp only [fin.lt_iff_coe_lt_coe, fin.coe_last, fin.coe_mk] at h,
simp [fin_rotate_of_lt h, fin.eq_iff_veq, fin.add_def, nat.mod_eq_of_lt (nat.succ_lt_succ h)] },
end
@[simp] lemma fin_rotate_apply_zero {n : ℕ} : fin_rotate n.succ 0 = 1 :=
by rw [fin_rotate_succ_apply, zero_add]
lemma coe_fin_rotate_of_ne_last {n : ℕ} {i : fin n.succ} (h : i ≠ fin.last n) :
(fin_rotate n.succ i : ℕ) = i + 1 :=
begin
rw fin_rotate_succ_apply,
have : (i : ℕ) < n := lt_of_le_of_ne (nat.succ_le_succ_iff.mp i.2) (fin.coe_injective.ne h),
exact fin.coe_add_one_of_lt this
end
lemma coe_fin_rotate {n : ℕ} (i : fin n.succ) :
(fin_rotate n.succ i : ℕ) = if i = fin.last n then 0 else i + 1 :=
by rw [fin_rotate_succ_apply, fin.coe_add_one i]
/-- Equivalence between `fin m × fin n` and `fin (m * n)` -/
@[simps]
def fin_prod_fin_equiv : fin m × fin n ≃ fin (m * n) :=
{ to_fun := λ x, ⟨x.2 + n * x.1,
calc x.2.1 + n * x.1.1 + 1
= x.1.1 * n + x.2.1 + 1 : by ac_refl
... ≤ x.1.1 * n + n : nat.add_le_add_left x.2.2 _
... = (x.1.1 + 1) * n : eq.symm $ nat.succ_mul _ _
... ≤ m * n : nat.mul_le_mul_right _ x.1.2⟩,
inv_fun := λ x, (x.div_nat, x.mod_nat),
left_inv := λ ⟨x, y⟩,
have H : 0 < n, from nat.pos_of_ne_zero $ λ H, nat.not_lt_zero y.1 $ H ▸ y.2,
prod.ext
(fin.eq_of_veq $ calc
(y.1 + n * x.1) / n
= y.1 / n + x.1 : nat.add_mul_div_left _ _ H
... = 0 + x.1 : by rw nat.div_eq_of_lt y.2
... = x.1 : nat.zero_add x.1)
(fin.eq_of_veq $ calc
(y.1 + n * x.1) % n
= y.1 % n : nat.add_mul_mod_self_left _ _ _
... = y.1 : nat.mod_eq_of_lt y.2),
right_inv := λ x, fin.eq_of_veq $ nat.mod_add_div _ _ }
/-- Promote a `fin n` into a larger `fin m`, as a subtype where the underlying
values are retained. This is the `order_iso` version of `fin.cast_le`. -/
@[simps apply symm_apply]
def fin.cast_le_order_iso {n m : ℕ} (h : n ≤ m) : fin n ≃o {i : fin m // (i : ℕ) < n} :=
{ to_fun := λ i, ⟨fin.cast_le h i, by simpa using i.is_lt⟩,
inv_fun := λ i, ⟨i, i.prop⟩,
left_inv := λ _, by simp,
right_inv := λ _, by simp,
map_rel_iff' := λ _ _, by simp }
/-- `fin 0` is a subsingleton. -/
instance subsingleton_fin_zero : subsingleton (fin 0) :=
fin_zero_equiv.subsingleton
/-- `fin 1` is a subsingleton. -/
instance subsingleton_fin_one : subsingleton (fin 1) :=
fin_one_equiv.subsingleton
|